Yield effect of applying earthworm castings produced during the oilseed rape-growing season in rice-oilseed rape cropping fields to rice - Min Huang (Nature Portfolio, 2018)
Abstract In-field earthworm density can be increased by planting oilseed rape during the non-rice growing season as compared to maintaining the rice-growing fields in fallow. This study was conducted to determine the effect on rice yield of earthworm castings produced during the oilseed rape-growing season in rice-oilseed rape cropping fields and to identify the critical factors that contribute to the yield effect. Field microplot experiments were conducted in 2016 and 2017. In 2016, a rice cultivar was grown under a factorial combination of absence (EC0: 0 kg m−2) and presence of earthworm castings (EC1: 17 kg m−2) with three N application rates (9, 12 and 15 g m−2). In 2017, nine rice cultivars were grown under EC0 and EC1 with the moderate N rate as was used in 2016. Results showed that application of earthworm castings produced during the oilseed rape-growing season in rice-oilseed rape cropping fields had a significant positive yield effect on rice. This was attributed to increased panicle m−2 and total aboveground biomass while spikelets panicle−1, spikelet filling percentage, grain weight, and harvest index were not affected. Our study indirectly provides a new evidence that oilseed rape is an excellent previous crop for cereals.